Zasebnost po Snowdnu - Završnik, Aleš (Zbornik znanstvenih razprav (Pravna fakulteta. 1991), 2014)
The article analyses recent theorizing of privacy arising from new technologies that allow constant and ubiquitous monitoring of our communication and movement. The theoretical part analyses Helen Nissenbaum's theory of contextual integrity of privacy and pluralistic understanding of privacy by Daniel Solove. The empirical part presents the results of an online survey on the Slovenian public perceptions of privacy that includes questions on types and frequency of victimizations relating to the right to privacy; self-reported privacy violations; concern for the protection of one's own privacy; perception of primary privacy offenders; the value of privacy; attitude towards data retention in public telecommunication networks; and acquaintance with the Information Commissioner of RS. Despite growing distrust of large internet corporations and - after Edward Snowden's revelations - Intelligence agencies, the findings indicate a low degree of awareness and care for the protection of personal data.
Keywords: človekove pravice; human rights; privacy; zasebnost; pravica do zasebnosti; pravna ureditev; javnost; javno mnenje; družbena omrežja